Working in the Field - Stewart, P. author. aut Link
XII, 95 p.
Keywords: How are ethnographic knowledge and anthropological theory created out of field experiences? Spanning Papua New Guinea, Taiwan, and Scotland, and Ireland, Stewart and Strathern show how fieldwork in apparently different areas can lead to unexpected comparisons and discoveries of similarities in human cross-cultural patterns of behavior.